Development of the Scratch: Coding for Kids Learning Module for Basic Programming Concepts in Elementary Schools - Satria Gunawan Zain; Mustari Lamada; Alfi Arista (Journal of Smart Education and Emerging Technology, 2026)
Background/Context: The development of digital technology has highlighted the importance of learning programming from elementary school age in order to foster children's computational thinking skills. Although Scratch offers an interactive and beginner-friendly visual learning approach, the limitations of learning modules that are still in English and have not been adapted to the age characteristics and cognitive abilities of children pose challenges in optimally understanding basic programming concepts. Objective/Purpose: This study aims to develop and assess the feasibility of Scratch modules tailored to the characteristics and cognitive abilities of elementary school children and to understand the basic concepts of programming. Method: This study used the Research and Development (R&D) method with a 4-D development model. Data were collected through a Likert scale questionnaire given to subject matter experts, media experts, and fifth-grade students at SD Inpres Kampus IKIP as test subjects. Data analysis was performed using quantitative descriptive statistics to assess the validity and feasibility of the developed Scratch module Results: : The Scratch learning module that was developed received very high validity scores from subject matter and media experts. Student feedback from pilot tests in small and large groups indicated a very positive level of practicality, with overall test results demonstrating that the module is highly effective in improving students' understanding of programming. Conclusion: The Scratch learning module that was developed has proven to be valid, practical, and effective as a teaching resource, and has the potential to support self-directed learning as well as structured and easy-to-understand coding instruction for elementary school students in introducing basic programming concepts across various schools.